Rancang Bangun Aplikasi Point Of Sales (POS) Terintegrasi Sistem Informasi Akuntansi Pada CV Mantu Sedana - Ni Luh Putu Kertiasih; Komang Tri Werthi; I Gede Juliana Eka Putra (Primakara University, 2020)
CV Mantu Sedana is a company engaged in the culinary business, in which the product sold is Balinese chili sauce. CV Mantu Sedana still uses the conventional method in their sales transactions and accounting records, where consumers who make purchases will get written notes and their accounting recording processes still use the manual method, namely by recording on books and agendas. Based on the writer’s explanation above and the needs of CV Mantu Sedana, the writer feels that it is necessary to build an application system or platform that can be used in the sales transaction process as well as accounting records at CV Mantu Sedana, which aims to make it easier for owners to monitor their business in real-time and increase consumer satisfaction. Design of Integrated Point Of Sales (POS) Applications for Accounting Information Systems at CV Mantu Sedana. The writer used the agile method in designing this application. The Agile method is one of the software development methodologies used in software development. In this study, the writer used an interview and observation research instruments. The instrument was addressed to the owner of CV Mantu Sedana which aimed to determine the needs for the system being designed. In this study, the writer used qualitative data types in which the data used were in the form of words, sentences, schemes, and images, in the form of descriptive non-numerical data collection. The results of this study indicated that in making application design at CV Mantu Sedana, it can provide solutions to companies in developing services to customers and problems the company faced. After conducting interviews on user satisfaction in using this point of sales application, thus the writer found that this application was able to overcome the problems and objectives of using this application itself.